2010
DOI: 10.1007/s13197-010-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-storage heat treatment on enzymological changes in peach

Abstract: Peach (Prunus persica (L.) Batsch) fruit was subjected to hot water and moist hot air treatment at varying temperatures. The activities of polyphenoloxidase (PPO) and polygalacturonase (PG) were monitored during storage for 0, 3 and 6 days. PPO activity decreased in all treatments during storage. This decrease was more in hot water treated fruits than in hot air. PPO activity decreased with the increase in treatment duration. However, the PG activity increased in heat treated fruits as well as control. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, enzymatic browning, which is mainly caused by a ployphenol oxidase (PPO), leads to a deleterious change in sensory properties of watermelon products (Jayaraman et al 1982;Walker and Ferrar 1998). Traditionally, thermal treatments were used to inactivate PPO (Yemenicioğlu et al 1997;Matsui et al 2007;Soysal 2008;Fortea et al 2009;Bakshi and Masoodi 2010). However, the thermal treatment leads to destruction of heat-sensitive nutrients and quality of food inevitably, such as: texture, color, and flavor (Flora 1976;Hayakawa et al 1977;Paulus and Saguy 1980;Chawla and Ranote 2009).…”
mentioning
confidence: 99%
“…However, enzymatic browning, which is mainly caused by a ployphenol oxidase (PPO), leads to a deleterious change in sensory properties of watermelon products (Jayaraman et al 1982;Walker and Ferrar 1998). Traditionally, thermal treatments were used to inactivate PPO (Yemenicioğlu et al 1997;Matsui et al 2007;Soysal 2008;Fortea et al 2009;Bakshi and Masoodi 2010). However, the thermal treatment leads to destruction of heat-sensitive nutrients and quality of food inevitably, such as: texture, color, and flavor (Flora 1976;Hayakawa et al 1977;Paulus and Saguy 1980;Chawla and Ranote 2009).…”
mentioning
confidence: 99%
“…Because of high respiration, peach fruit has a fast ripening process, so it cannot be stored for a long period at ambient temperature. It has a shorter storage life of 3-5 days at room temperature [6]. There are approximately 40% postharvest losses in peach fruit [7].…”
Section: Postharvest Complicationsmentioning
confidence: 99%
“…Results suggested that cooking treatment of the leaves resulted in significant (p<0.05) reduction of phenolic content (Figure 4.11). Numerous studies have been focused on the effect of cooking methods on dietary phytochemicals (Bellili et al, 2019;Ramírez-Jiménez et al, 2019;Zhao et al, 2019) as it affects the stability of compounds due to chemical and enzymatic decomposition, losses by volatilization or thermal decomposition (Adams, 1991;Bakshi & Masoodi, 2010;Cortés et al, 2006;Gonçalves et al, 2010). These factors also could be the main reason in the reduction of phenolic content in the leaves studies.…”
Section: Orac and Tpcmentioning
confidence: 99%
“…Present study discussed on the effect of fruit ripening and processing (raw versus boiled) of the unripe fruit and leaves of papaya. Heat is known to improve availability of some nutrients, inactivate enzyme activities that speed up nutrient damage, destroy undesirable microorganisms and food contaminants as well as favourably change the physical attributes of food (Adams, 1991;Bakshi & Masoodi, 2010;Cortés, Esteve, Rodrigo, Torregrosa, & Frígola, 2006;Gonçalves, Pinheiro, Abreu, Brandão, & Silva, 2010). Nevertheless, loss of nutrients is also one of the undesirable changes in food processing and should be tested.…”
Section: Introductionmentioning
confidence: 99%